Crises and response: Development & humanitarian aid in Middle East & North Africa - Kurdi, Sikandra; Bertini, Raffaele; Chaitani, Youssef; Jovanovic, Nina; Abdelfattah, Lina Alaaeldin (CGIAR, 2024)
This is a compilation of presentations used by speakers at the Bridging Evidence and Policy (BEP) Seminar Series: Crises and Response – Development and Humanitarian in the MENA, held last March 26, 2024 in Cairo, Egypt. The seminar is organized in collaboration between Sawiris Foundation for Social Development (SFSD), the International Food Policy Research Institute (IFPRI), and the Egyptian Food Bank (EFB) and is part of CGIAR’s National Policies and Strategies (NPS) Initiative.